1980
DOI: 10.1056/nejm198001243020402
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism

Abstract: We examined the incidence and clinical and economic consequences of primary hyperparathyroidism in residents of Rochester, Minn, from 1965 through 1976; 90 cases were found. From January 1, 1965, to June 31, 1974, the average annual incidence was 7.8 +/- 1.2 (mean +/- S.D.) cases per 100,000 population. However, after the introduction of routine measurement of serum calcium, the average annual incidence rose to 51.1 +/- 9.6 cases per 100,000. Even after availability of routine measurement of serum calcium, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
1
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 859 publications
(133 citation statements)
references
References 30 publications
6
125
1
1
Order By: Relevance
“…In our patients an increased prevalence of parathyroid adenomas, thyroid carcinomas, and adrenal adenomas was observed that was 10 times higher compared with the corresponding European population (2,18,19,20,21,22,23,24,25,26,27,28,29). However, this finding should be interpreted with caution, as it may be attributed to the extensive investigations and periodical assessment performed and to the mixed populations living in different European countries.…”
Section: Discussioncontrasting
confidence: 56%
“…In our patients an increased prevalence of parathyroid adenomas, thyroid carcinomas, and adrenal adenomas was observed that was 10 times higher compared with the corresponding European population (2,18,19,20,21,22,23,24,25,26,27,28,29). However, this finding should be interpreted with caution, as it may be attributed to the extensive investigations and periodical assessment performed and to the mixed populations living in different European countries.…”
Section: Discussioncontrasting
confidence: 56%
“…The cut-off value was adopted because most of the recommended levels of serum calcium, as an indication for surgery, range between 11.5 and 12.0 mg/dl [13,14,22], and even "conservative" physicians indicate pa rathyroidectomy when the level exceeds 12 mg/dl [12,15].…”
Section: Study Selectionmentioning
confidence: 99%
“…Primary hyperparathyroidism is a metabolic disorder resulting from excessive production of parathyroid hormone (PTH) and probably is the most common cause of hypercalcaemia in the general population [1]. Primary hyperparathyroidism is presented in a patient with impending renal failure due to systemic lupus erythematosus with antiphospholipid syndrome (SLE-aPLS).…”
Section: Introductionmentioning
confidence: 99%
“…Primary hyperparathyroidism is the most frequent cause of hypercalcemia as described in population-based epidemiologic studies [1]. Description of endocrine abnormalities in SLE has been limited in the literature.…”
Section: Introductionmentioning
confidence: 99%